Glomerulonephritis associated with deposition of hepatitis B surface antigen-antibody immune complexes in children - Ertuğrul, Meliha; Saatçi, Ümit (The Turkish Journal of Pediatrics, 1974)
Deposition of immunoglobulin G, HB_sAg and C_3 were shown by immunofluorescence in 3 kidney biopsy specimens from patients with clinical and laboratory diagnosis of glomerulonephritis. HB_sAg was found positive in the sera of two out of three patients. One of these patients had anicteric hepatitis and the others had a history of jaundice. The clinical features of the illness and laboratory data, support a role for Hepatitis B antigen in the development of the renal disease.